Developing Global Workforce: An Integrative Intercultural Effectiveness Model for International Human Resource Development - Pi-Chi Han (Adult Education Research Conference, 2012)
Globalization has a significant impact on the field of human resource development (HRD), especially on international HRD (IHRD). The challenge of developing global workforce with intercultural competencies has received extensive attention. It is necessary to reexamine the structure and content of IHRD programs that facilitate individual to be interculturally competent. This paper attempts to propose an integrative intercultural effectiveness (ICE) model, modified from Han‘s (2011) study, as the guidelines for IHRD to identify the process and content in developing intercultural competencies. Keywords: Intercultural Effectiveness (ICE) Competencies, Human Resource Development (HRD), International HRD (IHRD), Cross-cultural Learning, Transformative Learning
Keywords: Intercultural Effectiveness (ICE) Competencies; Human Resource Development (HRD); International HRD (IHRD); Cross-cultural Learning; Transformative Learning